Thrombin-activated Human Platelets Release two NAP-2 Variants that Stimulate Polymorphonuclear Leukocytes - Piccardoni, Paola; Evangelista, Virgilio; Piccoli, Antonio; de Gaetano, Giovanni; Walz, Alfred; Cerletti, Chiara (Thrombosis and Haemostasis, 1996)
Thrombin-activated human platelets release substance(s) of a prote-ic nature which induce an increase in the intracellular calcium concentration in polymorphonuclear leukocytes (PMN). Aim of this study was to characterize the platelet released product(s) responsible for PMN stimulation.PMN-stimulating activity was isolated from platelet supernatant by FPLC and HPLC. The N-terminal sequence analysis revealed that the purified fractions consisted in 90% of a peptide of 73 amino acids and in 10% of a peptide of 74 amino acids; both are truncated forms of the connective tissue-activating peptide III (CTAP-III), a platelet a-granule product, and have 3 and 4 additional amino acids at the N-terminus compared with the neutrophil-activating peptide 2 (NAP-2): Asp-Leu-Tyr and Ser-Asp-Leu-Tyr, respectively. Treatment of platelet supernatant (previously depleted of PMN-activating nucleotides) with Affi-gel heparin resulted in the disappearance of PMN-stimulating effects, suggesting that NAP-2 variants, which are heparin-binding proteins, account for ATP-independent PMN-stimulating activity of the supernatant. Cross-desensitization between rNAP-2 and the platelet supernatant and inhibition by the anti-NAP-2 antibody are in agreement with this conclusion. Although NAP-2 and its variants are reportedly generated from the inactive precursors, CTAP-III and platelet basic protein, through a proteolytic cleavage, NAP-2 variants were not generated in our system by proteases deriving from platelets or contaminating leukocytes. Indeed, treatment of intact platelet suspensions with different protease inhibitors failed to modify the calcium stimulating activity of the resulting supernatants. In conclusion, thrombin-activated platelets release NAP-2 variants which are not generated outside the platelets by proteolytic processing but are released in an active form. This finding enhances our understanding of platelet-PMN interaction in thrombosis and inflammation.